Celebrity Endorsement’s Impact on Female College Student Behavior: Investigating Bandwagon Effect, Hedonic, and Utilitarian Value - Harafah, Wa Ode Uswatun Miladina Putri; Maski, Ghozali; Prasetyia, Ferry (Jurnal Aplikasi Manajemen, 2024)
The rapid advancement of technology has transformed consumer behavior, leading to an increase in impulsive buying, particularly among the younger generation. This study explores the role of celebrity endorsements in driving impulsive online purchasing among female university students, focusing on how the bandwagon effect, hedonic value, and utilitarian value influence the urge to buy cosmetics impulsively. This study employed explanatory research utilizing a quantitative approach, focusing on 190 female students who actively engage with social media and follow internet celebrities. Data were collected through an online questionnaire distributed via social media. Structural Equation Modelling (SEM) was applied for data analysis. The findings reveal that the bandwagon effect directly enhances the urge to buy impulsively and strengthens the influence of both hedonic and utilitarian values on impulsive purchasing behavior. Additionally, hedonic and utilitarian values positively affect the bandwagon effect and the urge to buy impulsively. The emotional connection with celebrities and the perceived credibility of endorsed products are key drivers of impulsive purchases. This research contributes a deeper understanding of the psychological and social factors influencing impulsive buying in the digital age.